O que é um humano?: anotações sobre duas controvérsias - Rafael Antunes Almeida (2010)
This work is a study on two controversies, which are: the Valladolid debate,which opposed Bartolomé de Las Casas and Juan Ginés Sepúlveda around the question to know if the american indians were humans; the controversy that took place in Brazilian Supreme Court between 2005 and 2008, about the use of criopreserved embryos in the stem cell research. From the study of these debates, it is intended todiscuss the mechanisms operating in the definition of what counts as a human.